Public and Private Partnership: A Strategy to Repair Old Texture - Nakhaei, Mahdieh; Bandaryan, Esfandiar; Ezatpanah, Bakhtiar (Journal of History Culture and Art Research, 2017)
Todays, due to high construction costs and lack of economic potential of owners of old textures, public and private partnership is one of the restoration methods of these textures. Public-private partnership in the investment and implementation of worn and old textures’ restoration with guidance, support and supervision of governmental and public pillars is considered as a master key in restoration of old textures. This study aims at examining the effect of public and private partnership on restoration of old textures as well as providing strategies for strengthening and expanding this type of partnership. This article, based on descriptive-analytical approach, initially analyzes the existing problems and empowers the sections related to the rehabilitation and modernization of the textures. Then, through public and private partnership dealing with features such as shortening project times, reducing the project’s financial problems, having financial–technical power, adopting equal rights for partners, and using flexible planning. Further, according to the findings of this study, in the case of legal infrastructures for public-private partnership, compliance of urbanism criteria with major goals of urban textures’ modernization, adequacy of facilities and incentive packages, the cooperation of owners, an increase in the supervision of the relevant institutions on partnership and the use of local experts and investors, the success of this partnership and restoration may be stably guaranteed.